The Process of Remembering with the Forgotten Australians: Digital Storytelling and Marginalized Groups - Hancox, Donna (Human Technology, 2012)
Digital storytelling projects have proliferated in Australia since the early 2000s, and have been theorized as a means to disseminate the stories and voices of "ordinary" people. In this paper I examine through the case study of a 2009 digital storytelling project between the Australasian Centre for Interactive Design and a group identifying as Forgotten Australian whether digital storytelling in its predominant workshop-based format is able to meet the needs of profoundly marginalized and traumatized individuals and groups. For digital storytelling to be of use to marginalized groups as a means of communication or reflection a significant re-examination of the current approaches to its format, and its function needs to undertaken. This paper posits new ways of utilizing digital storytelling when dealing with trauma narratives.